PENGARUH PENERAPAN BLENDED LEARNING TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS PADA MATA KULIAH PROGRAM LINEAR - Raharjo, Sigit; Raihanah; Putri Sholihatul Ashar; Yuslinaini (LPPM - Universitas Serambi Mekkah, 2024)
This research is motivated by the current post-pandemic conditions which have caused lost learning which has an impact on student learning outcomes. This study aims to determine: Does the blended learning strategy have a significant effect on students' mathematical creative thinking abilities in linear program courses. The type of research used is quantitative research using the Pre-Experimental method. The population in this study were active students at the University of Muhammadiyah Tangerang, and through a probability sampling technique, the sampling technique used in this study was a saturated sampling technique where the sample was not randomly selected and there was no control variable. The population in this study were 5th semester students who took the Linear Program course. A sample of 20 people was obtained consisting of 5th semester mathematics education students. The data collection instrument used a mathematical creative thinking ability test. While testing the hypothesis using the t-test. It is known that more than 60% of students have a fairly high ability to think creatively mathematically, students do test questions using different methods and strategies. The results showed that blended learning-based learning had a significant influence on students' mathematical creative thinking skills in linear program courses.